Catalytic torrefaction of pelletized agro-residues with Cu/Al2O3 catalysts - Nakorn Tippayawong (2020)
© 2019, Springer-Verlag GmbH Germany, part of Springer Nature. The effect of the addition of a Cu/Al2O3 catalyst on the product distribution of gas-phase products during torrefaction of pelletized corn residues was investigated at temperatures between 220 and 300 °C. Pelletized corn residues were mechanically mixed with Cu/Al2O3 catalyst pellets. The mixture was then thermally treated in a fixed bed reactor for 40 min of residence time at low temperatures of wet flue gas simulated by O2 (4% v/v), CO2 (12% v/v), and steam (14% v/v), balanced with N2. The higher heating value (HHV) of torrefied pellets was also examined within the operating conditions. It was found that torrefaction temperature affected the product distribution, yields, and HHV significantly, while the presence of Cu/Al2O3 catalyst pellets promoted the conversion of CO to CO2 and the production of H2 from raw biomass pellets via CO oxidation and water-gas shift reactions. This finding provides a favorable outlook for the energy utilization of pelletized agro-residues via torrefaction with wet flue gas as a pretreatment method, in which inexpensive catalysts could be applied to eliminate toxic gases and/or generate valuable hydrogen during the torrefaction process.